Ocular injury and its associated factors among patients admitted to a hospital in Selangor - Tan, N. E.; Mohd Zaki, Nooraina; Goh, L. X.; S. A., Syed Muhammad; Adon, Mohd Yusoff; Ariffin, Ahmad Azuhairi; Mohd Isa, Muhammad (Community Health Society Malaysia, 2014)
Background: There are various factors associated with ocular injury such as age, gender, nationality, ethnicity, work related factor and alcohol intake. The aim of this study is to determine the proportion of ocular injury and its associated factors among patients admitted to a hospital in Selangor. Materials and Methods: A hospital-based cross-sectional study design and universal sampling method were used. Data collection was conducted in a hospital in Selangor by retrospective review of secondary data for last six months from data collection period. The data were transferred into a proforma. The data analysis was done using Statistical Package for Social Sciences (SPSS) version 20. Chi square test was done to determine the relationship between the associated factors of ocular injury. Result: There were 11 8 proforma collected. There were higher proportion of ocular injury in age group of 20-39 (59.3%), male (92.4%), Malay (47.5%) and Malaysian (65.3%). Cases of unilateral eye involvement were highest (88.1%) and occurred unintentionally (94.9%). Mostly (80.5%), patients sought immediate treatment after ocular injury. The commonest place of incident and source of ocular injury were industrial premises (33.1%) and blunt object (28.0%) respectively. 52.5% of ocular injury were of non penetrating diagnosis. There was high proportion of ocular injury due to work related factor (44.9%). Besides, there were significant relationship between types of nationality with work related factor (p=0.001) and types with sources of injury (p=0.001). There was no relationship between period of time taken before treatment with types of injury (p=0.118). Conclusion: In short, ocular injury is more common in age group of 20-39 years old, male, Malaysian and Malay. There is high proportion of ocular injury due to work related factor. There are also significant relationship between types of nationality with work related factor and types of ocular injury with sources of injury among patients with ocular injury.